Traditional genetic improvement and use of biotechnological techniques in searching of resistance to main fungi pathogens of Musa spp. - Michel Leiva-Mora (Biotecnología Vegetal, 2006)
Bananas and plantain are important food staple in human diet, even cooked or consumed fresh. Fungal diseases caused by Fusarium oxysporum f. sp. cubense (Foc) and Mycosphaerella fijiensis have threated to distroy Musa spp. Those crops are difficult to breed genetically because they are steriles, do not produce fertil seeds and they are partenocarpic. Genetic crossing by hibridization have been used successfully in FHIA and IITA Musa breeding programs, they have released numerous improved hybrids to those diseases. Plant Biotechnology has developed a set of techniques for Musa micropropagation to increase multiplication rates, healthy and safety plant material for plantation. Mutagenic techniques, somaclonal variation, somatic embryogenesis and more recient genetic transformation have enabled advances and complementation with clasical Musa breeding for searching resistance to principal fungal pathogen of Musa spp. Field evaluation systems to find Musa resistant genotypes to Foc and M. fijiensis have demostrated to be usefull but laborious. Nevertheless to enhance eficacy in selection of promissory genotypes the development of reproducible early evaluation methodologies by using fungal pathogens or their derivates is needed.